(untitled) (Journal of Environmental Science and Natural Resources, 2019)
An experiment was conducted at the Soil Science Field Laboratory of Bangladesh Agricultural University, Mymensingh during Aman season of 2016 to evaluate the effects of deep placement of N fertilizers in the form of USG and NPK briquettes in comparison with PU on nitrogen use efficiency and yield of BRRI dhan49. The soil was silt loam in texture having pH 6.27, organic matter content 1.95% and total N 0.136%. The experiment was laid out in a RCBD with eight treatments and three replications. The PU was applied in three equal splits. The USG and NPK briquettes were deep placed at 10 DAT and the briquettes were placed at 8-10 cm depth between four hills at alternate rows. The maximum grain yield of 5981 kg ha-1 was recorded in T3 which was statistically similar with T2 and T6. The highest straw yield of 6381 kg ha-1 was observed in T3. The lowest grain yield (3265 kg ha-1) and straw yield (4280 kg ha-1) was recorded in T3. The deep placement of USG and NPK briquettes enhanced both the recovery of applied N and N use efficiency in comparison with broadcast application of prilled urea. J. Environ. Sci. & Natural Resources, 11(1-2): 53-58 2018